Alternative fiscal rules for the new EU member states - D. Mario Nuti (Transformation, Integration and Globalization Economic Research (TIGER), 2006)
The fiscal regime of new EU member states is dictated by the Stability and Growth Pact by virtue of EU membership and, for EMU candidates such as all new EU members are supposed to become soon, by the Maastricht Treaty. Such dual fiscal regime is somewhat perverse: Maastricht conditions in the year before EMU entry is assessed are significantly harder than SGP conditions before and after - a pointless hurdle. Most new members have fiscal difficulties: structural deficits, relatively low and mostly indirect taxation, widespread flat tax; failure to coordinate monetary and fiscal policy, and the fiscal shock of EU entry. The paper then discusses SGP criticisms and their relevance to CEE economies: neglect of the size of public debt, and of the share of public investment; failure to co-ordinate, within the Euro-area, both the fiscal policy of member countries, and the overall fiscal stance of the euro-area with ECB monetary policy; the inappropriateness of SGP rules to the principle of subsidiarity that shapes EU policy. The March 2005 reform has softened the SGP and considered some of these factors, but there is still considerable uncertainty in the EU authorities' discretionary powers, and Maastricht conditions remain rigid. The implications are likely delays in both fiscal consolidation and the introduction of the euro in many of the new eastern member states - unless they can get away with either cosmetic measures such as those pioneered by Italy and other member states, or unilateral euroisation - two options which are neither likely nor desirable. Recommendations include: 1) unification of fiscal deficit requirements of EU membership and EMU entry 2) formal non-discretionary modification of the fiscal deficit rules applicable to both EU and EMU in the directions of the March 2005 reform of SGP; 3) the relaxation of fiscal constraints for individual countries as long as the overall fiscal stance of the entire euroarea meets the criteria set for each country.
Keywords: 330; Finanzpolitik; Haushaltskonsolidierung; EU-Mitgliedschaft; EU-Mitgliedschaft